Dynamika zmian migracyjnych przed wejściem Polski do Unii Europejskiej - Adamczyk, Anita (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2008)
The migration to and through Poland formed a part of global processes that were shaped by such factors as wars, poverty and the violation of human rights. Since the early 1990s, Poles have become the witnesses to phenomena they never experienced before. Social and political reforms, the opening of Polish borders, liberalization of en- trance rules, and the beginning of the negotiations on Poland’s membership in the EU structures brought about irreversible changes in the social, political and economic realms. The migration processes that used to bypass Poland have become a reality. In the beginning of the 21stcentury we faced new challenges, related to the matters of refugee protection, increased crime rate among foreigners or illegal border crossing.
The Dynamics of Migration Changes Before Poland's Entry